Natural Hazard Risks on Railway Turnout Systems. (2016) - Dindar, Serdar; Kaewunruen, Sakdirat; An, Min; Osman, Mohd H.
Abstract: As an essential feature to enable rail operational flexibility, railway turnouts are special track systems used to divert a train from a particular direction or a particular track onto other directions or other tracks. Railway turnout is constructed on a complex geometry and grade, which makes it one of the most critical railway infrastructures. These characteristics pose various risks in rail operations. A considerable number of derailment incidents have occurred every year. Not only do these incidents yield operational downtime and financial losses, but they also give rise to the casualties and sometimes the loss of lives across the world. One of fundamental reasons is that railway industry barely pays attention to risk elements on railway turnouts. This paper thus presents how turnout components work as a system, the diversity of emerging risks considering natural hazards and global warming potential to the system. Additionally, in order to perform a well-designed quantitative-based risk analysis method for appropriate risk management of railway turnouts and crossings, focusing on aging, degradation and signalling faults on the systems, the research develops a number of new ideas.